Hyper-Cross-Linked Polymer on the Hollow Conjugated Microporous Polymer Platform: A Heterogeneous Catalytic System for Poly(caprolactone) Synthesis - Choi, Sung Jae; Choi, Eun Ho; Song, Changsik; Ko, Yoon Joo; Lee, Sang Moon; Kim, Hae Jin; Jang, Hye Young; Son, Seung Uk (ACS Macro Letters, 2019)
This work shows that the shape-controlled microporous organic polymer (MOP) can be utilized for the morphological engineering of another class of MOP materials. The morphology of a hyper-cross-linked polymer (HCP) was successfully engineered on the hollow conjugated microporous polymer (CMP). Through the postsynthetic modification of HCP bearing BINOLs (HCP-B) on the hollow CMP-like material (H-CMPL), the HCP bearing BINOL phosphoric acid (HCP-BP) was engineered on the H-CMPL platform. The resultant H-CMPL@HCP-BP showed good catalytic performance as a heterogeneous catalytic system and excellent recyclability in the ring-opening polymerization of ϵ-caprolactones to poly(caprolactone).
Keywords: Catalytic performance; Conjugated microporous polymers; Cross-linked polymers; Heterogeneous catalytic systems; Microporous organic polymers; Postsynthetic modification; Recyclability; Shape-controlled